Is Child Nutrition a Priority in Kerala? An Exploration of the Integrated Child Development Services Programme - Rajeev Jayalakshmi; Srinivasan Kannan (World Nutrition, 2025)
Background: Kerala, a southern state of India, is well known for its better health indicators, including child nutrition. However, the state’s efforts to tackle malnutrition have been relatively stagnant in the last decade. The present paper examines the prioritization of child nutrition in the political agenda of Kerala and the implementation of the Integrated Child Development Services (ICDS), the universal nutrition supplementation programme for children below five years in India.